IDEAL ELECTRONIC CONTRACT MODEL AS A FORM OF E-COMMERCE DISPUTES SETTLEMENT - Andi Aina Ilmih; A Zulkarnain (Jurnal Pembaharuan Hukum, 2019)
This study focuses on electronic contracts in the Indonesian Home Credits Financing Institution by analyzing the effect of electronic contracts on electronic transactions in Indonesia. Then find the ideal model of electronic contracts as a form of e-commerce legal dispute resolution. This study uses normative legal research methods, with a legal approach and a conceptual approach. Based on the research that has been done, the influence of electronic contracts in electronic transactions (e-commerce) in Indonesia has brought about major changes by changing the model of non-electronic (conventional) commercial transactions into electronic (modern) transactions and inspiring online dispute resolution. Then the ideal model of electronic contracts as a form of e-commerce legal dispute resolution in Indonesia, must contain 10 important things in the e-contract clause namely: 1. Freedom of Contract; 2). Offers and Receipts; 3). Good intention; 4). Use of Terms; 5). Risk Transfer; 6). Please Loss; (7). Emergencies; 8). Changing Contracts; 9). Termination reasons; 10). Choice of Law and Dispute Resolution online, as stated in the e-contract of Indonesian Home Credits.